Genetic parameters for visual scores, growth and carcass traits in Nellore Cattle - Soares, BYANKA Bueno; Brunes, Ludmilla C.; Baldi, Fernando Sebastian [UNESP]; Carmo, Adriana S. Do; Pereira, Letícia S.; Carvalho, Rafael A.; Narciso, Marcelo G.; Amorim, Sabrina T.; Sainz, Roberto Daniel; Magnabosco, Cláudio U. (FapUNIFESP (SciELO), 2024)
Growth and carcass traits are essential selection criteria for beef cattle breeding programs. However, it is necessary to combine these measurements with body composition traits to meet the demand of the consumer market. This study aimed to estimate the genetic parameters for visual scores, growth (pre and post-weaning weights), and carcass (rib eye area (REA), back and rump fat thickness) traits in Nellore cattle using Bayesian inference. Data from 12,060 animals belonging to the HoRa Hofig Ramos herd were used. Morphological traits were evaluated by the MERCOS methodology. The heritability estimates obtained ranged from low to high magnitude, from 0.15 to 0.28 for visual scores, 0.13 to 0.44 for growth, and from 0.42 to 0.46 for carcass traits. Genetic correlations between visual scores and growth traits were generally of moderate to high magnitudes, however, visual scores showed low correlations with carcass traits, except between sacral bone and structure and REA. Selection for visual score traits can lead to favorable responses in body weight and vice versa, but the same is not true for carcass traits. Morphological categorical traits can be used as complementary tools that add value to selection.
Keywords: Bayesian methods; genetic association; morphological traits; weight performance; Zebu Cattle